“GOD PREPARES THE WAY FOR HIS LIGHT TO ENTER INTO THE TERRIBLE DARKNESS OF MUSCOVY”. EXCHANGE AND MOBILITY BETWEEN HALLE PIETISM AND RUSSIAN ORTHODOX CLERGY IN THE 18TH CENTURY - HAAS, Daniel; LYUTKO, Eugene; RIMESTAD, Sebastian (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2023)
This contribution analyses the relationship between Halle Pietism and Russian Orthodoxy with a focus on the mobility of actors on both sides. This included Halle Pietists travelling to Russia, but also young Russians being invited to Halle to study theology. The paper uses unpublished sources from the Archives of the Francke Foundations in Halle to paint a comprehensive picture of this mobility of people, but also of ideas and literature, which might not have achieved the intended aims on either side, but was still an important episode in German-Russian relations that has received very little attention in existing research. The relationship is looked at over four distinct chronological stages from the final decade of the 17th century to the Catherinian era in the 1760s, with an additional section focusing on the Russian academic migration to Halle. Each of these stages must be seen both within the context of what happened in Russia at this time, as well as the developments in Halle. This paper takes all these aspects into account.